Comparison of multilocus sequence typing (MLST) and repetitive sequence-based PCR (rep-PCR) fingerprinting for differentiation of Campylobacter jejuni isolated from broiler in Chiang Mai, Thailand - Prapas Patchanee (2018)
We compared rapid fingerprinting using repetitive sequence-based PCR (rep-PCR) for subtyping Campylobacter jejuni isolates to the widely used multilocus sequence typing (MLST). Representative C. jejuni isolates (n = 16) from broilers were analyzed using MLST and rep-PCR. Both techniques demonstrated an equal discriminatory power of 0.8917, and 9 subgroups were identified. Clonal identification of all 16 isolates was identical for both techniques. The rep-PCR as described in this study may be used as a rapid and cost-effective alternative for subtyping of C. jejuni isolates, or as an effective screening tool in large epidemiological studies. © The Korean Society for Microbiology and Biotechnology.